ACTUAL PROVISIONS OF MECHANISMS OF DECISION-MAKING IN THE EU - Zhamaladen, Ибрагимов; Жанар Серикбаевна, Даирова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
Article is devoted to important aspects of activity international the organizations connected with a decision-making order. Also in article insufficient study of the coordinated procedural mechanisms of decision-making which would consider all variety of the European association is noted. Authors pays attention of researchers to improvement actual position of mechanisms of decision-making in the European Union